2020
DOI: 10.1103/physrevb.101.054424
|View full text |Cite
|
Sign up to set email alerts
|

Magnon damping in the zigzag phase of the Kitaev-Heisenberg- Γ model on a honeycomb lattice

Abstract: We calculate magnon dispersions and damping in the Kitaev-Heisenberg model with an offdiagonal exchange Γ and isotropic third-nearest-neighbor interaction J3 on a honeycomb lattice. This model is relevant to a description of the magnetic properties of iridium oxides α-Li2IrO3 and Na2IrO3, and Ru-based materials such as α-RuCl3. We use an unconventional parametrization of the spin-wave expansion, in which each Holstein-Primakoff boson is represented by two conjugate hermitian operators. This approach gives us a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 100 publications
(188 reference statements)
4
18
0
1
Order By: Relevance
“…It should be noted that our analysis was performed using a classical model, while we could expect quantum fluctuations to renormalize the excitation spectra or to cause energy and momentum broadening of the intensity, as reported in other low-dimensional frustrated magnets [54,[58][59][60][61]. Furthermore, a recent analysis of α-RuCl 3 has shown that the presence of off-diagonal terms ( and ), causing the spins to tilt out of the honeycomb plane, could induce magnon decay [40,52,62]. This effect would be expected at twice the energy of the main magnon branch and therefore could explain the discrepancies above 6 meV in both compounds, where the scattering is broad in energy and momentum.…”
Section: Discussionmentioning
confidence: 80%
“…It should be noted that our analysis was performed using a classical model, while we could expect quantum fluctuations to renormalize the excitation spectra or to cause energy and momentum broadening of the intensity, as reported in other low-dimensional frustrated magnets [54,[58][59][60][61]. Furthermore, a recent analysis of α-RuCl 3 has shown that the presence of off-diagonal terms ( and ), causing the spins to tilt out of the honeycomb plane, could induce magnon decay [40,52,62]. This effect would be expected at twice the energy of the main magnon branch and therefore could explain the discrepancies above 6 meV in both compounds, where the scattering is broad in energy and momentum.…”
Section: Discussionmentioning
confidence: 80%
“…We also point out that an apparent visibility of the magnon modes in LSWT S (Q, ω) in the vicinity of the Γ point at low fields, Figure 3(f),(g), and lack thereof in the experimental data, Figure 3(a-c), can be explained by a significant interaction of the single-magnon branch with the two-magnon continuum. While the quantitative calculation of such effects in the anisotropic-exchange models is quite involved [51,52] and is beyond the scope of the present work, we, nevertheless, provide an intuitive insight into it by showing the bottom of the two-magnon continuum for three magnetic domains in Figure 3(f) and (g). As shown by the dashed lines in Figure 3 for both 0 T and 2.5 T, the bottom of the continuum has lower energy than one magnon modes at the large portion of the Brillouin zone, including the Γ point.…”
Section: S (Q ω) For Select Parametersmentioning
confidence: 90%
“…For S = 1/2 systems, such an overlap can lead to strong decays and near-complete disappearance of the well-defined magnon excitations in the corresponding range of momenta together with the other phenomena such as strong renormalization of the single-magnon branches [53,54]. These effects require significant coupling between one-and two-magnon sectors -an inevitable consequence of the anisotropic exchange terms in (1), which are allowed by the presence of strong spin-orbit coupling in the rare-earth-based and some transition-metal compounds [29,51,55].…”
Section: S (Q ω) For Select Parametersmentioning
confidence: 99%

Phase Diagram of YbZnGaO4 in Applied Magnetic Field

Steinhardt,
Maksimov,
Dissanayake
et al. 2021
Preprint
Self Cite
“…Here, we focus on α-RuCl 3 , which magnetically orders below 7 K in zero field and reveals magnon excitations at low energies [13][14][15][16][17][18]. Additionally, it shows broad high-energy spectral features that are often interpreted as fractionalized excitations -vestiges of the proximate QSL state [13,[19][20][21][22] -although this behavior can also be described in terms of magnon decays and incoherent excitations originating from strong magnetic anharmonicities [23][24][25][26]. In-plane magnetic fields lead to a gradual suppression of magnetic order that completely disappears around B AF2 c 7.5 T [27][28][29][30][31] (see also the inset of Fig.…”
mentioning
confidence: 99%